Seed yield structure in taiga and sub-settlement Siberian stone pine forests: level, and nature of differences - Velisevich Svetlana; Popov Alexander; Goroshkevich Sergei (E3S Web of Conferences, 2023)
On the example of Siberian stone pine, seed productivity was analysed in two stands that differed in origin and formation conditions. The cone yield was analysed in years with different levels of seed production in the period from 2016 to 2019. In terms of the number of cones per tree, the sub-settlement Siberian stone pine forest was 2-3 times superior to the taiga Siberian stone pine forest. The level of individual variability in the number of cones in the near-settlement Siberian stone pine forest was significantly lower than in the taiga forest. There is reason to believe that the high level of variability is likely related to a more pronounced differentiation of the stand by crown size. The number of dead ovules in the Siberian stone pine forest in settlement is 60-70% higher than in the taiga forest. Due to high “mortality” of ovules and high variability of this trait, the number of filled seeds in the near-settlement Siberian stone pine forest is much lower, and variability in the number of complete seeds is much higher than in taiga Siberian stone pine forest. When there are few filled seeds in a cone, the size of each of them increases. Therefore, the average weight of one filled seed is higher in the subsettlement Siberian stone pine forest than in the taiga forest. Thus, the quality of the cones in the years of average and especially high yield in the near-settlement Siberian stone pine forest is much lower, and the level of variability of the traits that characterise it is much higher, and the distribution of the traits is characterised by a pronounced negative kurtosis. Obviously, these peculiarities of the near-settlement Siberian stone pine forest are related to human interference in the course of its development, which disturbed the course of natural selection and deformed the genotypic composition of the population.